PEMBINAAN AKHLAK SANTRIWATI PONDOK PESANTREN MODERN DARUL ISTIQAMAH PUTRI KABUPATEN HULU SUNGAI TENGAH - Mardiana Mardiana (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to describe the implementation of moral education for female students at the Modern Islamic Boarding School Darul Istiqamah Putri in Hulu Sungai Tengah District and to identify the factors hindering and supporting such moral education. The research method employed a descriptive qualitative approach. Data collection techniques in this study include observation, interviews, and documentation. The results of this study indicate that female students are consistently guided, nurtured, provided with understanding, and given examples through various efforts by the female teachers through activities that serve as means for character development, which are found to be quite effective and well-established. The factors hindering moral education include parents who do not fully support the boarding school's regulations, a less religious hometown environment, and a lack of seriousness among female students in pursuing their studies. On the other hand, the supporting factors include a religious boarding school environment and the presence of the Modern Boarding School Organisation (OPPM).